The Therapeutic Effect of Mesenchymal Stem Cells in Spinal Cord Injury - Negargar, Sohrab; Pooladi, Marziyeh; Hatami, Fariba; Bahrani, Seyed Shahabeddin; Kargar Jahromi, Hossein (Galen Medical Journal, 2022)
Spinal cord injury (SCI) is an injury of the spine that could be life-threatening and lead to partial or complete loss of autonomic, sensory, and motor function below the injured area. Surgery decompression and steroid injection are the current treatments for SCI, but neither is particularly effective, and there is a growing demand for a more potent treatment. Mesenchymal stem cells (MSCs) are novel therapeutic agents that were used in different inflammatory diseases. These cells have immunomodulatory and regenerative properties which make them a promising candidate for neurological disorders such as SCI. MSCs are easily expandable in vitro and have the capacity for multilineage differentiation. These cells, which can be derived from adipose tissue, bone marrow (BM), Wharton jelly, or umbilical cord, have immunomodulatory and paracrine capabilities. They can release a variety of cytokines and other substances that suppress the growth of B cells, T cells, and natural killer cells (NKCs) as well as alter the activity of dendritic cells (DCs). In this study, we reviewed clinical studies that showed the effects of MSCs from different sources in the SCI.